Literature Study of Pasang Ri Kajang as a Guideline for Resolving Customary Violations in the Ammatoa Kajang Customary Law Community - Kurnia Ali Syarif (International Journal of Education, Vocational and Social Science, 2022)
The Ammatoa indigenous people of the Kajang tribe have a cultural institution called. They live exclusively in the Area known as the Ammatoa Customary Area. The distances from the sub-district capital, regency capital and provincial capital to the location of customary areas are: 25 km, 57 km and 270 km respectively. The life of the indigenous people who live in the customary area is called the Ilalang embayyah (Kajang Dalam) area where the indigenous people adhere to or are guided by "Pasang Ri Kajang", namely in the form of messages, wills, advice, mandates that are sacred in nature and are legally obligatory to implement. This research is a Literature Study by tracing the results of scientific publications with a vulnerability of 2019-2022 with the keyword Pasang Ri Kajang. The search was carried out through the Adabiyah Journal, Equilibrium, ALDEV, and Google Scholar databases. Based on the results of a literature search with the keyword Pasang Ri Kajang, 490 results were obtained, then screening which articles were Free Full Text (n: 312), and identified based on which titles were close to research (n: 51), screening based on abstract identification by looking at the results and research methods (n: 28), identify the feasibility of the remaining articles (n: 7), in order to obtain 5 articles that are in accordance with the research objectives.